Knowledge management in the desing of welding joints - Kaminskas, Tomas; Kulvietis, Genadijus; Keblas, Leonas (Lietuvos matematikos rinkinys, 2005)
In the process of welding the objective and subjective factors areexisting and the defects of welded joints may occur under their influence. The higher level of welded joints can be reached while using the weld joint design on the computer based programme. The expert system and it stucture of non-defect design of welded joints has been reviewed in the work. The programme helps to select the optimal welding parametres and allows decreasing of objective and subjective defects to occur as well as correcting welding arametres if any defect occurs.